Astrosphaeriella is polyphyletic, with species in Fissuroma gen. nov., and Neoastrosphaeriella gen. nov. - Liu, Jian-Kui; Phookamsak, R.; Jones, E.B.G.; Zhang, Y.; Ko-Ko, T.W.; Hu, Hong-Li; Boonmee, S.; Doilom, M.; Chukeatirote, E.; Bahkali, A.H.; Wang, Y.; Hyde, K.D. (2011)
Collections of fungi from bamboo and palm plants in Thailand resulted in the identification of several species of Astrosphaeriella, including the type species A. fusispora, which is a synonym of A. stellata. Species of Astrosphaeriella have been previously circumscribed on the basis of morphology and, to a lesser extent, on host affiliation. In order to obtain a phylogenetic understanding of the genus, eleven strains of Astrosphaeriella sensu lato were sequenced in this study. Molecular analyses based on a combined dataset of 18S and 28S nrDNA sequences were carried out to infer the phylogenetic placement of these strains in the Pleosporales. The phylogenetic analyses showed that Astrosphaeriella is polyphyletic, with Astrosphaeriella species clustering in four clades, two clades, including species with slit-like ostioles, clustered in Aigialaceae; the clade that includes the generic type clustered together with Delitschia; and A. Africana, which has striate ascospores, deviated from these three clades and had a basal position in the Pleosporales. A new combination in Fissuroma gen. nov. and new genus Neoastrosphaeriella are introduced in Aigialaceae to include the species with slit-like ascomata.